2022
DOI: 10.3889/oamjms.2022.9937
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pumpkin Seed Biscuits on Nutritional and Zinc Status: A Randomized Controlled Trial in Pregnant Women

Abstract: BACKGROUND: In several studies in Indonesia, low birth weight (LBW) is shown as the most dominant risk factor for stunting. Some of the causes of LBW are chronic energy deficiency during pregnancy, anemia during pregnancy, lack of nutrient supply during pregnancy, pregnancy complications, maternal parity, and birth spacing. In this case, women commonly suffer from micronutrient deficiencies including iodine, iron, Vitamin A, zinc, and folate. Related to this, about 80% of pregnant women in the world fulfill no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Yet, at the end of the intervention, both underweight and wasting of children improved, presumably due to the intervention. These results are in line with that of Syakur et al [36], who found that pregnant women who consumed a pumpkin seed biscuit gained weight on average, as compared to those who ate a placebo biscuit. Improvement in underweight and wasting is expected as body weight responds quickly, as compared to increases in height [37].…”
Section: Anthropometrics Of Childrensupporting
confidence: 92%
See 1 more Smart Citation
“…Yet, at the end of the intervention, both underweight and wasting of children improved, presumably due to the intervention. These results are in line with that of Syakur et al [36], who found that pregnant women who consumed a pumpkin seed biscuit gained weight on average, as compared to those who ate a placebo biscuit. Improvement in underweight and wasting is expected as body weight responds quickly, as compared to increases in height [37].…”
Section: Anthropometrics Of Childrensupporting
confidence: 92%
“…The high compliance for both the consumption of intervention and control suggest that these foods were well-liked. Syakur et al [ 36 ] in 2022 found that pumpkin seeds as a supplement in Indonesia improved zinc status in adults. A study was conducted by Syam et al [ 37 ] which assessed the effect of biscuit fortified using pumpkin seeds on nutritional intake, nutritional status, and plasma zinc level of the adolescent.…”
Section: Discussionmentioning
confidence: 99%
“…This together with proper Zinc supplementation helps to reduce the risk of preterm birth. In effect, maternal Zinc supplementation lowers the risk of preterm birth, however, no evidence of Zinc supplements on other fetal outcomes was reported (21).…”
Section: Discussionmentioning
confidence: 99%
“…Children who experience stunting are caused by the fact that while in the womb the child has experienced growth retardation or stunted growth while still in the womb (Triwahyuningsih et al, 2018). Some of the causes of LBW are chronic energy deficiency during pregnancy, anemia during pregnancy, lack of nutritional supply during pregnancy, pregnancy complications, maternal parity, and birth spacing (Syakur et al, 2022).…”
Section: Birth Weight With the Incidence Of Stuntingmentioning
confidence: 99%